The The textualized classroom: a key pedagogical strategy for the formation of children readers and writers - Ochoa Cáceres, Heisel; Medina Martinez, Diana; Lizeth Muñoz, Jenny; Jaimes Jaimes, Emilce (Rastros Rostros, 2023)
To teach reading and writing is to guide the child in knowledge, it is also interpretation and production of written symbols, but to educate in reading and writing is also to create spaces for the child to cultivate these abilities and explore all the possibilities that it offers, going to the encounter of knowledge, emotion, feeling and aesthetic pleasure.
Keywords: textualized; classroom; pedagogical; strategy; reading; writing